2005
DOI: 10.1007/s11748-005-0149-9
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary blastoma

Abstract: We describe a resected pulmonary blastoma in an 84-year-old male, the oldest of previously reported patients. A chest X-ray showed a 2 cm-sized abnormal shadow in the left lung field. Five months later computed tomography demonstrated a well-demarcated heterogenous mass, measuring 12 cm in diameter, in the left lower lobe of the lung. This mass was diagnosed as a carcinoma using echo-guided percutaneous biopsy. The patient underwent a left lower lobectomy. The resected specimen revealed the tumor to be a pulmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…5,6 Although CT-guided lung biopsy revealed malignant cells with sarcomatous elements in our case, it was diffi cult to diagnose BPB preoperatively.…”
Section: Discussionmentioning
confidence: 69%
“…5,6 Although CT-guided lung biopsy revealed malignant cells with sarcomatous elements in our case, it was diffi cult to diagnose BPB preoperatively.…”
Section: Discussionmentioning
confidence: 69%
“…Liver, central nervous system and bones are the most frequent locations of distant metastases [2]. A review of the literature revealed only few atypical cases: a rare case which presented as a solitary upper lip metastasis in a paraplegic male (diagnosis was confirmed by autopsy findings) [2], a case of pulmonary blastoma with endobronchial growth [13], a rare case of classic biphasic pulmonary blastoma in a 40-year-old Hispanic female [14], two atypical cases of Caucasian women, aged 21 and 41 years [7], and an 84-year-old male, the oldest patient reported [15]. It should be noted that the metastasis to the adrenal gland was not histologically proven; however, its enlargement upon disease progression strongly suggests metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment strategy should be defined by a multidisciplinary team that includes a pulmonologist, an oncologist, a thoracic surgeon and a general surgeon. It is essential that surgical treatment be considered as quickly as possible when such a tumor is suspected [15], andpossibly supported by adjuvant chemotherapy and/or radiotherapy [19,23]. …”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21] Koss and associates 22 reported the largest series of pulmonary blastomas to date (including monophasic and biphasic tumors), analyzing data for 52 patients, and found that the great majority of these tumors occur in adults, with a mean and median age at diagnosis of 35 years. Two children younger than 10 years of age also were included in this group of patients, however.…”
Section: Clinical Featuresmentioning
confidence: 99%